Conjugate addition of a silyl ketene acetal to alpha,beta-unsaturated lactones - Gnaneshwar, Rudhramyna; Sivaram, S (Synthetic Communications, 2006)
{Conjugate addition of a silyl ketene acetal [
International Conference on Nanomaterials (NANO 2005), Mepco Schlenk Engn Coll, Sivakasi, INDIA, JUL 13-15, 2005
Keywords: acetals; deprotection; MoO3/SiO2; protection

MgBr2-mediated ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated aldehydes and ketones with 1,3-dienes - Chavan, Subhash P.; Ethiraj, Krishna S.; Dantale, Shubhada W. (Synthetic Communications, 2007)
A facile, mild, and efficient methodology for the ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated ketones and aldehydes as dienophiles with various 1,3- dienes employing MgBr2 as the Lewis acid catalyst to furnish corresponding Diels-Alder adducts at ambient temperature is described.
Keywords: acetals; Catalysts; Diels-Alder reactions; dienes

Oxidation of benzylic alcohols and sulfides over LaCoO3 and TBHP - Patil, Mahesh L.; Maujan, Suleman R.; Borate, Hanumant B.; Uphade, Balu S. (Arkivoc, 2007)
A simple and efficient methodology has been described for the selective oxidation of secondary benzylic alcohols to the corresponding ketones. In contrast, primary benzylic alcohols afforded dimethyl acetals.
Keywords: acetals; benzylic alcohols; Oxidation; perovskite LaCoO3

Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids